1992
DOI: 10.1002/mrc.1260301012
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional NMR spectra of asbestinin diterpenes isolated from Briareum asbestinum (Pallas). Total stereochemical assignment by two‐dimensional NMR techniques

Abstract: The concerted application of two-dimensional phase-sensitive COSY, RELAY, ROESY and I3C-'H shift correlation spectroscopy in the structural elucidation and stereochemical assignment of a new asbestinin diterpene, (a-1 l-acetoxy-4-deoxyasbestinin-(D), is reported. The results reveal that these two-dimensional techniques are invaluable for the stereochemical assignment of proton resonances in the 4-deoxyasbestinin series which overlap in 'H NMR and homonuclear correlation spectra. KEY WORDS 2D NMR Phase-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…An impressive number of marine invertebrates have been found to have promising cytotoxic activity against a variety of cancer cell lines. One such invertebrate, the gorgonian octocoral Briareum asbestinum Pallas, has been the subject of intense investigation in our laboratory (1)(2)(3). The secondary compounds of B. asbestinum are unusually diverse and consist mainly of briarane and asbestinane class diterpenoids (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An impressive number of marine invertebrates have been found to have promising cytotoxic activity against a variety of cancer cell lines. One such invertebrate, the gorgonian octocoral Briareum asbestinum Pallas, has been the subject of intense investigation in our laboratory (1)(2)(3). The secondary compounds of B. asbestinum are unusually diverse and consist mainly of briarane and asbestinane class diterpenoids (4).…”
mentioning
confidence: 99%
“…Although produced by a different terpene cyclization pathway, both classes consist of bicyclic molecules with fused sixand ten-membered rings. We have recently reported the isolation and structures of nine tetracyclic diterpenes, 4-deoxyasbestinins A-D (1,2), and asbestinins 6-10 (3), from this gorgonian. These diterpenes were found to be active against several human tumor cell lines at a 1-10 µ level.…”
mentioning
confidence: 99%
“…The relative configurations of C-20, C-23, and C-24 were determined based on J-based configuration analysis [11]. In addition to the 3 J H,H values, 2,3 J C,H values were detected using hetero half-filtered TOCSY (HETLOC) [12,13], phase-sensitive COSY (PS-COSY) [14], and phase-sensitive HMBC (PS-HMBC) [15,16] spectra of 1 in CD 3 OD. The relative magnitudes of coupling constants assigned from the 3 J H,H and 2,3 J C,H values indicated that each of C-17-C-20, C-20-C-22, C-22-C-23, and C-23-C-24 bonds adopted a single dominant con-former (Figure 4), which was further supported by the ROESY correlations (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, a correlation between the acetate methyl group and the C19 methyl group as well as the correlation between the acetate methyl with the C1 methine provide important insights. The original structural assignment was based on the assumption that the cyclohexane ring of C2−C11 cyclized cembranoids must be locked into a boat conformation. , However, if true, then the observed acetate methyl NOEs are inconsistent with an α C11 flagpole acetate. More consistent with the observed NOESY data is a chair cyclohexane in which the C11 acetate resides on the β face and the C20 methyl is equatorial.…”
mentioning
confidence: 99%